2,2'-Bipyridyl Catalyzed Oxidation of Cyclanols by Quinolinium Bromochromate-Kinetic Study - Santhosh Kumar, V.; Rukmangathan, M. (Asian Journal of Chemistry, 2010)
Kinetic investigation in 2,2'-bipyridyl catalyzed oxidation of some cyclanols(cyclopentanol, cyclohexanol, cycloheptanol, cyclooctanol) by quinolinium bromochromate (QBC) in 60 % aqueous acetic acid medium in presence of mercuric (II) acetate as a scavenger have been studied. The reaction exhibits a first order rate dependence with respect to oxidant quinolinium bromochromate (QBC) and perchloric acid while it is fractional order in cyclanols and 2,2'- bipyridyl. The variation of ionic strength, Hg(OAc)2 and acrylonitrile have insignificant effect on reaction rate. Effect of varying dielectric constant of medium on the reaction rate has been studied. Activation parameters have been evaluated from Eyring plots by studying the reaction at different temperature. The rate law has been derived on the basis of obtained data.